Ukuzaji wa Kiswahili : dhima na majukumu ya asasi mbalimbali - Michira, Nyachae; Iribemwangi, P. I.; Mbatiah, Mwenda (2014)
On the role of different sectors in the growth of the Swahili language.
Includes bibliographical references and index.
Keywords: Swahili language -- Kenya